Illinois Dental Anesthesia and Sedation Survey for 2006 - Flick, William G (American Dental Society of Anesthesiology, 2007)
This is a 10-year follow-up survey of a 1996 study of all dentists in Illinois holding a permit to administer sedation or general anesthesia. The survey describes the scope of sedation and anesthesia services provided in dental offices in Illinois. A mail survey was sent to 471 dentists who were registered with the department of professional regulation to administer sedation or general anesthesia. Classification by specialty area of practice showed: 63% (84% in 1996) are oral and maxillofacial surgeons, 20% (11% in 1996) general dentists, 6% (5% in 1996) periodontists, 9% (0% in 1996) pediatric dentists, 1% (less than 1% in 1996) dentist anesthesiologists. Advanced cardiovascular life support (ACLS) training was reported by 90% (85% in 1996) of the respondents. The total number of sedations and general anesthetics administered for the year was 115,940. Two mortalities and two cases of long-term morbidity were reported for the 10-year period. Respondents reported that 30 patients required transfer to a hospital but suffered no long-term morbidity. Other practice characteristics were detailed.